LOCAL TRAFFIC AND PUBLIC TRANSPORT PORTRAITS: A CASE STUDY IN PADANG CITY - Yaldi, Gusri; Apwiddhal, Apwiddhal; Nur, Imelda M.; Momon, Momon (FSTPT Indonesia, 2015)
This paper discusses the portraits and problems of local transport in Padang city related to some national issues which could represent the same condition in other cities in Indonesia too. It was found the private motor vehicles number on the road, especially motor cycles, is significantly higher compared to public transports. However, the public transport service tends to remain as the main transport mode in Padang, despite its decreasing percentage of usage. There were two kinds of public transports in term of mode sizes, namely the Para-transits (a passenger size public transport with maximum seat or passenger number is 11) and Medium size buses (maximum seat number is 26). However, the Medium size buses tend to be extinct and were found no longer operated since 2012. Meanwhile, the existing train service is mainly used for intercity trips although it has been existed since more than a century ago with the railway network is parallel with the major arterial roads crossing the Padang city. These figures seem to indicate the weak public transport planning and management. The local government launched newly developed Bus Rapid Transit service in February 2014. Although it might be considered premature, the recorded passenger number tends to be decreasing and hence and would end up like previous the medium size buses. The local government is suggested to address these issues seriously in order to minimize the negative impacts and potential economic loss of transport sector.